Molecularly Imprinted Solid-phase Extraction for the Selective Determination of Ciprofloxacin Designer Drugs in Pharmaceutical Preparations - Yehya Kamal Al-Bayati (Journal of Global Pharma Technology, 2016)
We have developed a new method with high sensitivity, low cost and high stability. Using a functional monomer, this method is based on a molecular polymer (MIP).Which is 2 (Trifluoromethyl) acrylic acid (TFMA), 3 (Trimethoxysilyl) propylmethacrylate (TMSA),suitable cross linker and ciprofloxacin (CPF) template for the production of monolithic solid phase micro extraction (SPME) fiber. Used_ UV. Vis_ as (detector).All these analytical methods used to extract, preconcentration and selective Ciprofloxacin determination (CPF). Competence, The stability and duration of the manufactured fiber plays a fundamental and indispensable role in SPME. The aim of this study is to examine the factors influencing the polymerization and extraction procedures, as well as to explain the selectivity of the manufactured fiber in the CPF solution. Also related and unrelated compound selectivity .Under optimum conditions. For five patients repeated experiments for three measurements the relative standard deviations) RSD percent are range of at (10ـ50)ppm of CPFH)Percentage (2.57ـ3.25). The relative recoveries obtained for CPF are within the range of (95.40 ـ 99.28) in spiked human urine samples.Keywords: Ciprofloxacin / Molecularly imprinted polymer solid-phase extraction / UV. Vis.